PENGGUNAAN METODE ANALITYCAL HIERARCHY PROCESS (AHP) DALAM PENENTUAN LOKASI PRIORITAS PEMBANGUNAN DRAINASE DI KOTA JAMBI: Location for Drainage, Analitycal Hierarchy Process (AHP), CodeIgniter, PHP MyAdmin - Kahar, Novhirtamely; Yudi Branata, Fajar (LP2M Universitas Nurdin Hamzah, 2018)
This study aims to build a software application for Decision Support System (DSS) Determination of Priority Location for Drainage Development in the City of Jambi by applying the Analitycal Hierarchy Process (AHP) method. In determining the priority location of drainage development by the Sumatra Regional Office VI based on submission by the community and then resolved. During this time, the selection process is sometimes subjective, so sometimes the drainage that is built is not a priority. In the application that is built, in the selection process, determining the priority location is based on certain criteria so that the decision can be more objective. There are several criteria, namely: land, infrastructure and social conditions. While the drainage location in Jambi City is an alternative. The method used is the AHP method, which is a method that makes a comparison of each criteria and alternative as well as the method that tests the consistency of the value of the criteria weight. The SPK application in this study was built with PHP Codeigniter with Wampserver and PHP MyAdmin database. From the results of the study, it was obtained the value of the location with the highest ranking that would be recommended for priority drainage construction, namely: 0.532 located at the TalangBakung location in Jambi City. With this application, it can help the decision making process by the leadership of Sumatra Regional Office VI with more objective and impartial.